Vector calculus - Marden, Jerrold E. (W. H. Freeman and company, 2003)
Now in its fifth edition, Vector Calculus helps students gain an intuitive and solid understanding of this important subject. The book’s careful account is a contemporary balance between theory, application, and historical development, providing it’s readers with an insight into how mathematics progresses and is in turn influenced by the natural world.